Saturation of the linear methods of summation of Fourier series in the spaces S pφ - Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider the problem of the saturation, in the spaces S pφ , of linear summation methods for Fourier series, which are determined by the sequences of functions defined on a subset of the space C. We obtain sufficient conditions for the saturation of such methods in these spaces.